1987
DOI: 10.1016/0035-9203(87)90300-2
|View full text |Cite
|
Sign up to set email alerts
|

Reliable assessment of malaria prevalence through village clinics

Abstract: In 4 villages in the Pakistani Punjab, clinic surveys (CS) provided similar results on total malaria and malaria species prevalence as those from mass surveys (MS)--and at a fraction of the effort. This was true at 3 different levels of malaria transmission. Both methods requiring blood films from all interviewed subjects are believed to be superior to the classical active (ACD) and passive (PCD) case detection methods which sample only patients with a history of recent fever. These latter methods would not de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…As with the present study, the weakest correlation was also reported for TPR among individuals aged � 15 years in the moderate (rho = 0.32) and high transmission areas (rho = 0.01) [43]. A much earlier study, outside of Africa, in Punjab, Pakistan, found a stronger positive correlation (rho = 0.97) between clinic slide positivity data and community survey data from four villages compared at three different periods of observation [42].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As with the present study, the weakest correlation was also reported for TPR among individuals aged � 15 years in the moderate (rho = 0.32) and high transmission areas (rho = 0.01) [43]. A much earlier study, outside of Africa, in Punjab, Pakistan, found a stronger positive correlation (rho = 0.97) between clinic slide positivity data and community survey data from four villages compared at three different periods of observation [42].…”
Section: Discussionsupporting
confidence: 66%
“…Several examples of the use of routine TPR data exist to understand the sub-national variations in malaria risk [26][27][28][29][30], at smaller spatial scales to define temporal trends [31][32][33][34][35][36][37], or intervention impact [38][39][40][41]. However, there have been few direct comparisons between community-based parasite prevalence and facility-based TPR [24,42,43]. Here the relationship between time-space matched TPR at health facilities and community-based prevalence of infection on the Kenyan coast was examined.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,33 The results of this study indicate that health facility-derived serological, parasitological, and molecular measures can detect differences in transmission intensity at a small geographical scale and are sensitive to seasonal changes. These findings suggest that health facility surveys are able to provide a reasonable measure of community-level transmission, are capable of delineating areas of high or low malaria transmission and that the use of serology and PCR added useful information to assessment of transmission levels in the sampled populations that would have been missed if sampling focused solely on those cases suspected of having malaria.…”
Section: Discussionmentioning
confidence: 78%
“…In both cases, these biases would work against the principal patterns presented here. Fox and Strickland (1989) noted that their conclusions relied on a prior demonstration by Fox et al (1987) that the overall and species-specific prevalences found in surveys of village clinic attendees sufficiently mimicked those in community surveys. Because 16 of the P. falciparum-P. vivax studies used here acquired data either through clinics or with other techniques that collect blood only in cases of self-reported recent fevers, neither of which are random surveys of the population, we were concerned that the higher overall prevalence in these studies might bias our findings.…”
Section: Resultsmentioning
confidence: 99%